Fe-N5 monatomic catalyst as well as preparation method and application thereof
By preparing the Fe-N5 single-atom catalyst TCN-Fe, the existing catalyst loading is solved, the problems of low synthesis, and poor stability are achieved, and ultra-fast degradation of quinolones and excellent degradation performance in high salinity wastewater are achieved.
Patent Information
- Application Number
- CN202411790024.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
AI Technical Summary
The existing single-atom catalyst for activated persulfate used for treatment of quinolones antibacterial contaminants has low loading, difficulty in synthesis and poor stability.
Using the preparation method of Fe-N5 single atom catalyst, the Fe-N5 single atom catalyst was prepared by mixing melamine and urea and calcining, followed by mixing with iron salt and ligand, and pyrolysis and acid etching treatment, the Fe-N5 single atom catalyst TCN-Fe was prepared.
The catalyst has a high specific surface area, exhibits ultra-fast degradation ability for a variety of antibiotics such as LEV, and has excellent degradation performance in high salinity wastewater systems, and can effectively reduce the biotoxicity of antibiotics in water.
Smart Images

Figure CN119793505A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment, and in particular to a Fe-N5 single atom catalyst and a preparation method and application thereof. Background Art
[0002] As people's living standards continue to improve, more and more new organic pollutants that are difficult to degrade enter the water body. Traditional water treatment technology can no longer meet the requirements for the effective removal of these pollutants.
[0003] Quinolone antibiotics, such as levofloxacin (LEV), are usually used as a broad-spectrum antimicrobial agent in animal husbandry and clinical practice. Since LEV is not easily removed by traditional sewage treatment processes, its residual concentration in wastewater, surface water and groundwater is often detected at the ng / L-μg / L level, posing a potential hazard to biological communities and human health. At present, the main removal methods of quinolone antibiotics include membrane treatment technology, electrochemical reduction and advanced oxidation technology. Among them, advanced oxidation technology has a high efficiency in removing emerging organic pollutants by producing highly active free radicals, and is favored by researchers, especially persulfate-based advanced oxidation technology.
[0004] The main ways to activate persulfate for advanced oxidation include thermal activation, photoactivation and transition metal activation. Among these activation methods, the first two consume a lot of energy, and the latter has the risk of metal ion leakage, causing secondary pollution. Therefore, the development of a new type of catalyst with high catalytic activity to activate persulfate and achieve rapid and efficient degradation of quinolone antibiotics is the focus of current research. Among the existing catalysts for activating persulfate, the commonly used single-atom catalysts have problems such as low metal loading, difficult synthesis, and poor stability.
[0005] In summary, a new single-atom catalyst with high stability, high activity, high selectivity and simple preparation for activating persulfate to degrade quinolone antibiotic pollutants in water bodies needs to be developed urgently. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a Fe-N5 single-atom catalyst and a preparation method and application thereof, so as to solve the problems of low loading, difficult synthesis and poor stability of the existing single-atom catalyst for activated persulfate used for the treatment of quinolone antibiotic pollutants.
[0007] The technical solution of the present invention to solve the above technical problems is as follows:
[0008] A method for preparing a Fe-N5 single-atom catalyst comprises the following steps:
[0009] (1) Mixing melamine and urea, grinding, and calcining to obtain tubular g-C3N4;
[0010] (2) mixing the tubular g-C3N4 and ligand mixed solution obtained in step (1) with an iron salt solution, stirring and evaporating, to obtain a precursor;
[0011] (3) The precursor obtained in step (2) is first pyrolyzed, then etched with acid solution, and finally washed and dried to obtain the product.
[0012] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a Fe-N5 single-atom catalyst, which has the characteristics of economy, safety, environmental protection and high efficiency. The preparation method is simple, the raw materials are cheap and easy to obtain, and the prepared single-atom catalyst has a high specific surface area, and exhibits ultra-fast degradation ability for a variety of antibiotics such as LEV. It has excellent degradation performance in high-salinity wastewater systems, and can effectively reduce the biological toxicity of antibiotics in water during the degradation process, and has huge practical application potential.
[0013] Furthermore, in step (1), the mass ratio of melamine to urea is (1-2): (10-20).
[0014] Preferably, in step (1), the mass ratio of melamine to urea is 1:10.
[0015] Furthermore, the calcination conditions in step (1) are: heating to 500-550° C. at a heating rate of 1-5° C. / min and calcining for 2-4 hours.
[0016] Preferably, the calcination conditions in step (1) are: heating to 520° C. at a heating rate of 3° C. / min and calcining for 3 h.
[0017] The beneficial effects of adopting the above further technical solution are: the present invention provides a method for preparing tubular g-C3N4, the raw materials for preparation are cheap and easily available, the preparation method is simple, and the specific surface area of g-C3N4 is effectively increased.
[0018] Furthermore, in step (2), the ligand is o-phenanthroline; and the iron salt is Fe(NO3)3·9H2O or FeCl3·6H2O.
[0019] Furthermore, in step (2), the mass ratio of iron salt, tubular g-C3N4 and ligand is (0.05-0.5):(2-4):(0.05-0.6); the volume ratio of the mixed solution of tubular g-C3N4 and ligand to the iron salt solution is (1-10):(1-2), and the volume ratio of the solvents of the mixed solution of tubular g-C3N4 and ligand to the iron salt solution is (0.5-2):(0.5-2).
[0020] Preferably, in step (2), the mass ratio of iron salt, tubular g-C3N4 and ligand is 0.202:3:0.2703; the volume ratio of the mixed solution of tubular g-C3N4 and ligand to the iron salt solution is 10:2, and the volume ratio of the solvents of the mixed solution of tubular g-C3N4 and ligand to the iron salt solution is 1:1.
[0021] Furthermore, in step (2), the temperature of stirring and evaporating is 70-90° C. and the time is 20-30 h.
[0022] Preferably, the stirring evaporation temperature in step (2) is 80° C. and the time is 24 h.
[0023] Furthermore, the pyrolysis conditions in step (3) are: heating to 600-800°C at a heating rate of 3-7°C / min under a protective gas atmosphere, pyrolyzing for 1-3h and then cooling to room temperature.
[0024] Preferably, the pyrolysis conditions in step (3) are: heating to 700° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, pyrolyzing for 2 h, and then cooling to room temperature.
[0025] Furthermore, the acid solution in step (3) includes any one of hydrochloric acid solution, sulfuric acid solution and nitric acid solution, with a concentration of 0.05-0.2 mol / L; the drying temperature is 50-70° C., and the drying time is 5-12 h.
[0026] Preferably, the acid solution in step (3) is a hydrochloric acid solution with a concentration of 0.1 mol / L; the drying temperature is 60° C. and the drying time is 8 h.
[0027] A Fe-N5 single atom catalyst is prepared by adopting the preparation method.
[0028] Application of the above-mentioned Fe-N5 single atom catalyst in treating organic pollutants.
[0029] Furthermore, the organic pollutant is levofloxacin.
[0030] The present invention has the following beneficial effects:
[0031] The present invention uses tubular g-C3N4 as a carrier to prepare a tubular single-atom catalyst TCN-Fe with a Fe-N5 structure. The catalyst exhibits ultra-fast degradation of LEV and significant ultra-low-dose catalytic performance for a variety of antibiotics. Common inorganic anions or natural organic matter in water bodies not only do not have a negative impact on the degradation reaction, but also have a certain promoting effect. The catalyst has excellent degradation performance for high-salinity wastewater systems, and can also achieve biological detoxification of LEV through degradation, with significant economic, environmental and social effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the synthesis process of the TCN-Fe catalyst in Experimental Example 1;
[0033] Figure 2 The nitrogen adsorption-desorption curves and pore size distribution diagrams of TCN-Fe0.5 and tubular g-C3N4 in Experimental Example 1, wherein a) is the nitrogen adsorption-desorption curve, and b) is the pore size distribution diagram;
[0034] Figure 3 The XRD spectrum and Raman spectrum of the TCN-Fe catalyst in Experimental Example 1, wherein a) is the XRD spectrum and b) is the Raman spectrum;
[0035] Figure 4 SEM, TEM, HRTEM, HAADF-STEM, EDS and AC-HAADF-STEM images in Experimental Example 1, wherein a) is the SEM image of tubular g-C3N4, b) is the SEM image of TCN-Fe0.5, c) is the TEM image of TCN-Fe0.5, d) is the HRTEM image of TCN-Fe0.5, e) is the HAADF-STEM of TCN-Fe0.5 and the corresponding EDS element mapping image, and f) is the AC-HAADF-STEM image of TCN-Fe0.5;
[0036] Figure 5 The XANES and EXAFS results of Fe foil, Fe3O4 powder, FeO powder, Fe2O3 powder and TCN-Fe0.5 in Experimental Example 1 are shown in Figure 1, where a) is the XANES graph, the inset is a partial enlarged view of the absorption edge, b) is the EXAFS graph, and c) is the Fourier transform k of TCN-Fe0.5. 3 Weighted Fe k-edge EXAFS spectrum, d) is the EXAFS fitting diagram of TCN-Fe0.5 in R space, e)-i) are the wavelet transform analysis diagrams of the Fe element K absorption edge EXAFS spectra of Fe foil, Fe3O4 powder, FeO powder, Fe2O3 powder and TCN-Fe0.5 respectively;
[0037] Figure 6 The catalytic degradation curves of different catalysts on LEV in Experimental Example 2, wherein a) is the catalysts prepared in Example 3 and Comparative Example 1, and b) is the catalysts prepared in Examples 1 to 3;
[0038] Figure 7 The results of the optimization test of the catalytic degradation reaction in Test Example 2, wherein a) is different TCN-Fe0.5 concentrations, b) is different PMS concentrations, c) is different LEV initial concentrations, d) is different reaction temperatures, e) is different degradation systems, and f) is different catalysts for degrading LEV;
[0039] Figure 8 The catalytic degradation performance of different initial pH and different antibiotics in Experimental Example 3, wherein a) is the removal efficiency of TCN-Fe0.5 / PMS catalytic system for LEV at different initial pH, and b) is the catalytic performance of TCN-Fe0.5 catalyst for different antibiotics;
[0040] Fig. 9 The effects of different inorganic anions or natural organic matter on the catalytic degradation of LEV in Experimental Example 3, where a) is FA, b) is HA, and c) is CO3 2- , d is)HCO3 - , e) is H2PO4 - , f) is HPO4 2- , g) is Cl - , h) is NO3 - ;
[0041] Fig.10 This is a diagram showing the degradation effect of LEV in the actual water sample in Test Example 3;
[0042] Fig.11 The XRD spectrum and Raman spectrum of TCN-Fe0.5 before and after the degradation reaction in Experimental Example 3, wherein a) is the XRD spectrum and b) is the Raman spectrum;
[0043] Fig.12 The high-resolution Fe 2p and high-resolution N1s spectra of TCN-Fe0.5 before and after the degradation reaction in Experimental Example 3, wherein a) and b) are high-resolution Fe 2p, and c) and d) are high-resolution N1 s;
[0044] Fig.13 This is the LEV degradation pathway diagram in Experimental Example 3;
[0045] Fig.14 The results of toxicity analysis of LEV degradation intermediates in Experiment 3, where a) is mutagenicity and b) is rat LD 50 , c) is the LC value for Daphnia magna 50 , d) is developmental toxic. DETAILED DESCRIPTION
[0046] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0047] Embodiment 1:
[0048] A method for preparing a Fe-N5 single-atom catalyst comprises the following steps:
[0049] (1) Preparation of tubular g-C3N4: 0.5 g of melamine and 5 g of urea were mixed and ground for 15 min. After grinding evenly, the mixture was placed in an alumina crucible and heated to 520 °C at a heating rate of 3 °C / min in an air atmosphere. The mixture was calcined for 3 h to obtain solid tubular g-C3N4.
[0050] (2) Preparation of precursor: First, Fe(NO3)3·9H2O (404.0 mg, 1 mmol) was dissolved in 10 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) to obtain a transparent orange-red homogeneous solution; then the obtained solution was added to 50 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) containing g-C3N4 (3 g) and o-phenanthroline (540.6 mg, 3 mmol) and stirred evenly; finally, the obtained mixed solution was vigorously stirred and evaporated at 80°C for 24 h to dryness to obtain a precursor.
[0051] (3) Preparation of Fe-N5 single atom catalyst: The precursor powder obtained in step (2) was first placed in a tubular furnace, heated to 700°C (nitrogen atmosphere) at a heating rate of 5°C / min, pyrolyzed for 2 hours and then cooled to room temperature; the pyrolysis product was then placed in 50mL of 0.1mol / L hydrochloric acid solution for etching to remove unstable and inactive iron oxides; finally, it was washed with warm water and ethanol three times each, and dried overnight at 60°C in vacuum to obtain the Fe-N5 single atom catalyst TCN-Fe1.
[0052] Embodiment 2:
[0053] A method for preparing a Fe-N5 single-atom catalyst comprises the following steps:
[0054] (1) Preparation of tubular g-C3N4: 0.5 g of melamine and 5 g of urea were mixed and ground for 15 min. After grinding evenly, the mixture was placed in an alumina crucible and heated to 520 °C at a heating rate of 3 °C / min in an air atmosphere. The mixture was calcined for 3 h to obtain solid tubular g-C3N4.
[0055] (2) Preparation of precursor: First, Fe(NO3)3·9H2O (60.6 mg, 0.15 mmol) was dissolved in 10 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) to obtain a transparent orange-red homogeneous solution; then the obtained solution was added to 50 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) containing g-C3N4 (3 g) and o-phenanthroline (81.09 mg, 0.45 mmol) and stirred evenly; finally, the obtained mixed solution was vigorously stirred and evaporated at 80°C for 24 h to dryness to obtain a precursor.
[0056] (3) Preparation of Fe-N5 single atom catalyst: The precursor powder obtained in step (2) was first placed in a tubular furnace, heated to 700°C (nitrogen atmosphere) at a heating rate of 5°C / min, pyrolyzed for 2 hours and then cooled to room temperature; the pyrolysis product was then placed in 50mL of 0.1mol / L hydrochloric acid solution for etching to remove unstable and inactive iron oxides; finally, it was washed with warm water and ethanol three times each, and dried overnight at 60°C in vacuum to obtain the Fe-N5 single atom catalyst TCN-Fe0.15.
[0057] Embodiment 3:
[0058] A method for preparing a Fe-N5 single-atom catalyst comprises the following steps:
[0059] (1) Preparation of tubular g-C3N4: 0.5 g of melamine and 5 g of urea were mixed and ground for 15 min. After grinding evenly, the mixture was placed in an alumina crucible and heated to 520 °C at a heating rate of 3 °C / min in an air atmosphere. The mixture was calcined for 3 h to obtain solid tubular g-C3N4.
[0060] (2) Preparation of precursor: First, Fe(NO3)3·9H2O (202.0 mg, 0.5 mmol) was dissolved in 10 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) to obtain a transparent orange-red homogeneous solution; then the obtained solution was added to 50 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) containing g-C3N4 (3 g) and o-phenanthroline (270.3 mg, 1.5 mmol) and stirred evenly; finally, the obtained mixed solution was vigorously stirred and evaporated at 80°C for 24 h to dryness to obtain a precursor.
[0061] (3) Preparation of Fe-N5 single atom catalyst: The precursor powder obtained in step (2) was first placed in a tubular furnace, heated to 700°C (nitrogen atmosphere) at a heating rate of 5°C / min, pyrolyzed for 2 hours and then cooled to room temperature; the pyrolysis product was then placed in 50mL of 0.1mol / L hydrochloric acid solution for etching to remove unstable and inactive iron oxides; finally, it was washed with warm water and ethanol three times each, and dried overnight at 60°C in vacuum to obtain the Fe-N5 single atom catalyst TCN-Fe0.5.
[0062] Comparative Example 1:
[0063] A method for preparing a Fe-N5 single-atom catalyst comprises the following steps:
[0064] (1) Preparation of g-C3N4: 5 g of melamine was placed in an alumina crucible, heated to 520°C at a heating rate of 3°C / min in an air atmosphere, and calcined for 3 h to obtain light yellow solid g-C3N4.
[0065] (2) Preparation of precursor: First, Fe(NO3)3·9H2O (404.0 mg, 1 mmol) was dissolved in 10 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) to obtain a transparent orange-red homogeneous solution; then the obtained solution was added to 50 mL of deionized water and anhydrous ethanol (volume ratio of 1:1) containing g-C3N4 (3 g) and o-phenanthroline (540.6 mg, 3 mmol) and stirred evenly; finally, the obtained mixed solution was vigorously stirred and evaporated at 80°C for 24 h to dryness to obtain a precursor.
[0066] (3) Preparation of Fe-N5 single atom catalyst: The precursor powder obtained in step (2) was first placed in a tubular furnace, heated to 700°C (nitrogen atmosphere) at a heating rate of 5°C / min, pyrolyzed for 2 hours and then cooled to room temperature; the pyrolysis product was then placed in 50mL of 0.1mol / L hydrochloric acid solution for etching to remove unstable and inactive iron oxides; finally, it was washed with warm water and ethanol three times each, and dried overnight at 60°C in vacuum to obtain Fe-N5 single atom catalyst SA-FeCN (FeCN-700).
[0067] Test Example 1: Structural Characterization
[0068] (1) Synthesis Overview
[0069] Schematic diagram of the synthesis process of Fe-N5 single atom catalyst Figure 1 The present invention controls the amount of metal iron salt added to synthesize iron single-atom catalysts with different metal contents, and quickly synthesizes g-C3N4 with a tubular structure by mixing and grinding melamine and urea and performing high-temperature pyrolysis, thereby effectively increasing the specific surface area of the carrier, improving the exposure of active sites on the catalyst surface, and thus improving the catalytic performance.
[0070] (2) Nitrogen adsorption-desorption curve and pore size distribution
[0071] The pore size distribution and specific surface area of the catalyst and tubular g-C3N4 prepared in Example 3 were tested using the Brunauer-Emmett-Telle method (BET, Micrometrics / ASAP 2460).
[0072] The experimental results are as follows Figure 2 shown.
[0073] The experimental results show that compared with the ordinary flake g-C3N4 (specific surface area 11.51m 2 / g), the tubular g-C3N4 (45.88m 2 / g) significantly increased the specific surface area by about 2.98 times; by loading the tubular g-C3N4 to prepare the catalyst, the specific surface area of the catalyst can be effectively increased. The specific surface area of the catalyst prepared in Example 3 reached 78.22m 2 / g, providing more space for the reaction on the catalyst surface.
[0074] (3) XRD and Raman spectrum analysis
[0075] XRD (TD-3500) was used to obtain the diffraction spectrum of the catalyst crystal structure and image composition. The specific operating conditions were Cu target, Kα radiation The scanning range is 5-90°. Raman (Witec α300 accesses) is used to analyze the graphitization and defect degree of the catalyst. The excitation light wavelength is 352 nm.
[0076] The experimental results are as follows Figure 3 shown.
[0077] XRD showed that the catalysts prepared in Examples 1-3 had two broad peaks, and no peaks corresponding to iron nanocrystals were observed. The results showed that there were no crystalline Fe species on the catalyst, proving the high dispersion of Fe single atoms. The two characteristic peaks at 26° and 44° corresponded to the 002 and 100 crystal planes of graphite carbon, which were attributed to the interlayer stacking of the conjugated aromatic structure of g-C3N4.
[0078] In the Raman spectrum, the D band (1350 cm -1 ) and G belt (1580cm -1 ) intensity ratio (I D / I G ) reflects the graphitization degree and defect degree of the catalyst. D / I G It decreases with the increase of iron loading content. x The site is formed by a single Fe atom and a CN defect. The reduction of CN defect sites after the introduction of Fe is related to the consumption of nitrogen defect sites, which further indicates the successful preparation of the catalyst materials in Examples 1-3 of the present invention.
[0079] (4) Surface morphology and element analysis
[0080] The morphology and microstructure of the catalyst were observed using scanning electron microscopy (SEM, ZEISS Sigma 300) and transmission electron microscopy (TEM, FEI Talos F200S), and the distribution of each element of the catalyst was observed using an X-ray spectrometer (EDS). The dispersion of metal atoms in the single-atom catalyst was observed using a spherical aberration-corrected scanning transmission electron microscope (STEM, FEI Titan G2 60-300) and a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM, FEI / Themis Z).
[0081] The experimental results are as follows Figure 4 shown.
[0082] like Figure 4 From the SEM results of Figure a), it can be seen that the present invention successfully prepared tubular g-C3N4, and the morphology of the iron single atom material (Example 3) synthesized by further loading iron atoms with TCN-Fe0.5 still remained a tubular structure, as shown in Figure 4 As shown in Figure b). Figure 4 From the TEM results of Figure c), it can be seen that the catalyst material prepared in Example 3 of the present invention has no obvious attached nanoparticles or aggregation; Figure 4 As shown in Figure d), the catalyst materials prepared in Example 3 of the present invention are all slightly curled onion-shaped, without obvious long and straight lattice fringes corresponding to Fe metal, which confirms the amorphous nature of the single-atom iron catalyst prepared in the present invention, which is consistent with the XRD and Raman results. Figure 4 Figure e) shows that the Fe, C, N and O elements contained in the sample are evenly distributed on the catalyst surface. Figure 4 In the middle f), it can be observed that there are no Fe nanoparticles or clusters, indicating that the Fe element in the catalyst prepared in the embodiment of the present invention is dispersed on the g-C3N4 nanotubes at the atomic level. The above results all demonstrate the successful preparation of the tubular iron single-atom catalyst of the present invention.
[0083] (5) XANES and EXAFS analysis
[0084] The metal content of the catalyst was measured by ICP-OES (Agilent / 5110).
[0085] The X-ray absorption fine structure spectrum (XAFS) of single atom catalysts was measured using the 14W1B beamline of the Shanghai Synchrotron Radiation Facility (SSRF). The IFEFFIT software package was used to process the X-ray absorption near-edge structure spectrum (EXAFS) and extended transformed X-ray absorption fine structure spectrum (XANES), and the metal atoms on the catalyst were analyzed.
[0086] The experimental results are as follows Figure 5And as shown in Table 1.
[0087] The loading amount of Fe atoms in the single-atom catalyst TCN-Fe0.5 was determined by ICP-OES to be 6.4%, which is at a relatively high loading level. In order to verify the local environment coordination information and valence state of the Fe single-atom active center under morphology regulation, XANES and EXAFS were used to analyze the local environment of TCN-Fe0.5. At the same time, the XANES and EXAFS spectra of standard samples Fe foil, Fe3O4 powder, FeO powder, and Fe2O3 powder were used for comparison.
[0088] Figure 5 (a) The normalized XANES spectra of the Fe element K absorption edge of TCN-Fe0.5 and the corresponding benchmark samples are shown in the inset, and the enlarged part of the near-edge absorption is shown in the inset. The absorption edge energy of the TCN-Fe0.5 sample is between FeO and Fe2O3, and is closer to the standard spectrum of Fe3O4, indicating that it has Fe δ+ (2<δ<3) oxidation state, therefore, the electrons of Fe can be transferred to the neighboring N atoms. Compared with Fe foil, the absorption edge position of TCN-Fe0.5 shifts to higher energy; compared with Fe3O4, the absorption edge position of TCN-Fe0.5 shifts to lower energy, which is due to the regulation of the local coordination environment of the single-atom Fe metal center.
[0089] Figure 5 Figure b) shows the EXAFS spectra of TCN-Fe0.5 and related benchmark comparison samples, which clearly show the changes in the local coordination environment of the single-atom Fe metal center. Only one major isolated peak was observed at , which was attributed to the Fe-N bond of TCN-Fe0.5 and no metallic Fe-Fe The characteristic peaks of the iron atoms were confirmed to be dispersed successfully.
[0090] The Fe-N coordination of the first shell in the TCN-Fe0.5 single atom catalyst was confirmed again by wavelet transform analysis (WT). Figure 5 As shown in Figure e) and Figure i), no obvious Fe-Fe coordination was detected, confirming that the Fe atoms were successfully atomically dispersed in the carbon matrix.
[0091] Further, other structural parameters are extracted from the EXAFS fitting spectra of the Fe element K edge in different spaces, such as Figure 5 Figure c) and Figure d), the specific parameters are shown in Table 1. The results prove that the single-atom Fe metal center presents a 5-coordinated axial structure, and all structures prove that the present invention successfully synthesized the axially coordinated Fe-N5 single-atom catalyst through the morphology adjustment strategy of tubular g-C3N4 compared with Comparative Example 1.
[0092] Table 1 EXAFS fitting parameters of Fe-K edge of different samples
[0093]
[0094] Note: CN is the coordination number; R is the distance between atoms; σ 2 is the squared relative displacement, which is used to account for thermal and structural disorder; ΔE0 is the internal potential correction; and R-factor indicates the goodness of fit.
[0095] Test Example 2: Levofloxacin (LEV) degradation experiment
[0096] The activity of PMS was evaluated by the degradation of antibiotics in water by catalyst activation. The specific operation was as follows: a reaction bottle containing 30 mL of a certain concentration of antibiotic solution was placed in a constant temperature oscillating box (25°C, 200 rpm), and a certain concentration of PMS and catalyst were added in sequence. During the reaction, 1 mL of the suspension was taken as a sample at a specified time interval, then filtered using a 0.22 μm nylon membrane, and added to 0.2 mL of methanol to terminate the reaction. All experiments were repeated three times, and all other control experiments were carried out according to this procedure.
[0097] The concentration of LEV was determined by high performance liquid chromatography (Aglient 1260, USA). The chromatographic system used a TC-C18 (4.6 mm × 150 mm, 5 μm) column and a UV detector. LEV detection conditions: the mobile phase was acetonitrile: phosphate buffer (phosphoric acid and triethylamine modulated aqueous solution, pH = 3) = 30%: 70% (volume ratio), the flow rate was 0.8 mL / min, the UV-visible spectrophotometer was used for determination at a wavelength of 290 nm, the column temperature was 30°C, and the injection volume was 10 μL.
[0098] The experimental results are as follows Figure 6 and Figure 7 shown.
[0099] like Figure 6 As shown, the experiment was conducted by adding 1mmol / L PMS and 40mg / L catalyst to the initial concentration of 10mg / L LEV. The results show that under the same conditions, compared with the SA-FeCN catalyst prepared in Comparative Example 1, the TCN-Fe0.5 prepared in Example 3 of the present invention exhibits significantly stronger degradation performance on LEV, and can achieve a degradation effect of 93% in only 2 minutes. The corresponding degradation pseudo-first-order kinetic constant k obs 1.2621min -1 , which is 3.8 times that of comparative example 1. Figure 6 As shown in Figure b), among the catalysts prepared in Examples 1-3, TCN-Fe0.5 has the most significant catalytic degradation performance and is the best embodiment of this application.
[0100] In order to further optimize the physical quantities of the catalytic degradation reaction and seek the optimal reaction conditions, the present invention evaluated four aspects: TCN-Fe0.5 dosage, PMS usage, initial LEV concentration and reaction temperature. The experiment was carried out with fixed initial PMS concentration of 1.0 mmol / L, initial LEV concentration of 10 mg / L, initial TCN-Fe0.5 dosage of 40 mg / L and initial reaction temperature of 25 °C.
[0101] The experimental results are as follows Figure 7 As shown in the figure, the degradation efficiency of LEV increases with the increase of TCN-Fe0.5 concentration, but the degradation effect when its concentration increases to 60mg / L is equivalent to that of 50mg / L. This phenomenon is caused by the limited amount of PMS, which is in line with the general law of chemical reactions. The optimal catalytic conditions of the present invention are: initial LEV concentration 10mg / L, PMS concentration 1.0mmol / L, TCN-Fe0.5 dosage 40mg / L, reaction temperature 25℃. Figure 7 As can be seen from Figures e) and f), LEV is hardly removed in the system with only PMS or TCN-Fe0.5. Compared with different homogeneous and heterogeneous iron catalytic systems, the catalyst prepared in the present invention has the performance of ultra-fast and efficient degradation of LEV.
[0102] Test Example 3: Application in actual wastewater treatment
[0103] The TCN-Fe0.5 prepared in Example 3 was used as a catalyst for actual wastewater treatment. The experimental method and specific parameters were the same as the optimal catalytic conditions obtained in Experimental Example 2.
[0104] (1) Experiments were conducted by changing the pH of the catalytic reaction (3-11) and different antibiotics (DOX, CZB, FZD, OTC, LMF, GAT and TC, all at a concentration of 10 mg / L).
[0105] The experimental results are as follows Figure 8 As shown, the results show that the TCN-Fe0.5 catalyst exhibits high catalytic performance in a wide pH range (pH = 3-11), and has excellent degradation performance for multiple types of antibiotics, indicating that it has good environmental universality.
[0106] (2) Inorganic anions and natural organic matter are commonly found in actual wastewater, which have a negative impact on free radical AOPs, but have no substantial impact on non-free radical AOPs. 2- 、HCO3 - , Cl - 、NO3 - 、H2PO4- and HPO4 2- ) and two kinds of natural organic matter (NOM) were used to experiment on the TCN-Fe0.5 / PMS system.
[0107] The experimental results are as follows Fig. 9 As shown in the figure, 0-10 mg / L FA and HA had no inhibitory effect on the degradation of LEV within 2 min, which has important practical significance in actual water treatment. 2- 、HCO3 - , Cl - 、NO3 - 、SO4 2- 、H2PO4 - 、HPO4 2- Among the effects on catalytic degradation performance, in addition to HPO4 2- In addition, the other five inorganic anions have different degrees of promotion on the degradation of LEV, and with the increase of inorganic anion concentration, the promotion of degradation increases to different degrees, which is related to the adsorption capacity between the catalyst and inorganic ions and PMS. 2- and HCO3 - The free radicals in high oxidation state can be converted into low oxidation state. However, the catalyst prepared by the present invention is in the catalytic system, even in the high concentration of CO3 2- and HCO3 - In the presence of , no inhibitory effect on LEV was detected, but it had an excellent promoting effect, reflecting the unique degradation advantage of the non-free radical pathway.
[0108] The above results indicate that the catalytic degradation system of the catalyst prepared in the present invention has good environmental adaptability and excellent degradation ability under high concentration inorganic anion conditions, which is of great practical significance in actual water treatment, especially in high-salinity wastewater treatment.
[0109] (3) Study on LEV degradation in actual water samples
[0110] The optimal catalytic conditions obtained in Experimental Example 2 were used to conduct LEV degradation experiments on simulated high-salinity groundwater, fresh groundwater, tap water (Nanchong, Sichuan), lake water (China West Normal University), and Jialing River water (taken from Nanchong, Sichuan). The experimental results are shown in Figure 2. Fig.10 As shown, the results show that high-salinity water environment has a promoting effect on the degradation of LEV, indicating that the catalyst system prepared by the present invention has practical application value.
[0111] (4) Catalytic stability
[0112] The TCN-Fe0.5 catalyst after catalytic degradation reaction was characterized again. The experimental results are as follows Figure 11-Figure 12 And as shown in Table 2.
[0113] like Fig.11 As shown, the XRD and Raman spectra of TCN-Fe0.5 after the degradation reaction have almost no changes compared with those before the catalytic reaction, indicating that TCN-Fe0.5 has good stability before and after the reaction.
[0114] Table 2 Comparison of element contents of TCN-Fe0.5 before and after reaction
[0115]
[0116] like Fig.12 As shown in Table 2, the XPS analysis results after the degradation reaction showed that the valence state of the metal elements did not change significantly before and after the reaction, indicating that the TCN-Fe0.5 single atom catalyst has good stability.
[0117] In summary, the TCN-Fe0.5 single-atom catalyst prepared in Example 3 of the present invention has good stability and has prospects for practical application.
[0118] (5) Detoxification of LEV degradation
[0119] The intermediates produced during the degradation of LEV were analyzed by LC-MS-MS, such as Fig.13 Based on the mass spectrometry analysis, there are four possible degradation pathways. 1 After degradation by O2, most of LEV was eventually degraded into small molecules P11 (m / z=60) and P12 (m / z=57).
[0120] TEST was used to evaluate the toxicity of LEV and its degradation intermediates, including mutagenicity, rat LD 50 and Fathead Minnow LC 50 and developmental toxicity.
[0121] The experimental results are as follows Fig.14 As shown in the figure, the mutagenicity value of LEV is 0.67, which is determined to be a mutagenic chemical. After the initial degradation reaction, the mutagenicity is significantly reduced, and the mutagenicity of most intermediates after further oxidation is further reduced to low mutagenic substances. 50 As the evaluation object, it can be seen that the toxicity of the final product P12 is negligible, and the detoxification purpose is basically achieved. Fig.14 Acute toxicity LC values of fathead minnow in Figures c) and d) 50 The developmental toxicity of the intermediates further illustrates the detoxification effect of TCN-Fe0.5 / PMS on LEV.
[0122] In summary, the TCN-Fe0.5 / PMS system constructed by the catalyst prepared in the present invention can not only effectively and ultra-fast degrade LEV, but also be accompanied by biological detoxification during the degradation process. It is a "green" technology that shows great practical application potential in degrading organic pollutants such as antibiotics from water environments.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Fe-N5 single atom catalyst, characterized in that: The following steps are involved: (1) Mixing melamine and urea, grinding, and calcining to obtain tubular g-C3N4; (2) mixing the tubular g-C3N4 and ligand mixed solution obtained in step (1) with an iron salt solution, stirring and evaporating, to obtain a precursor; (3) The precursor obtained in step (2) is first pyrolyzed, then etched with acid solution, and finally washed and dried to obtain the product.
2. The method for preparing the Fe-N5 single atom catalyst according to claim 1, characterized in that: The mass ratio of melamine to urea in the step (1) is (1-2): (10-20).
3. The method for preparing the Fe-N5 single atom catalyst according to claim 1, characterized in that: The calcination conditions in step (1) are: heating to 500-550° C. at a heating rate of 1-5° C. / min and calcining for 2-4 hours.
4. The method for preparing the Fe-N5 single atom catalyst according to claim 1, characterized in that: In the step (2), the ligand is o-phenanthroline; and the iron salt is Fe(NO3)3·9H2O or FeCl3·6H2O.
5. The method for preparing the Fe-N5 single atom catalyst according to claim 1, characterized in that: In the step (2), the mass ratio of the iron salt, tubular g-C3N4 and the ligand is (0.05-0.5):(2-4):(0.05-0.6); the volume ratio of the mixed solution of tubular g-C3N4 and the ligand to the iron salt solution is (1-10):(1-2), and the volume ratio of the solvents of the mixed solution of tubular g-C3N4 and the ligand to the iron salt solution is (0.5-2):(0.5-2).
6. The method for preparing the Fe-N5 single atom catalyst according to claim 1, characterized in that: The stirring evaporation temperature in step (2) is 70-90° C. and the time is 20-30 hours.
7. The method for preparing the Fe-N5 single atom catalyst according to claim 1, characterized in that: The pyrolysis conditions in step (3) are: heating to 600-800° C. at a heating rate of 3-7° C. / min under a protective gas atmosphere, pyrolyzing for 1-3 hours and then cooling to room temperature.
8. The method for preparing the Fe-N5 single atom catalyst according to claim 1, characterized in that: The acid solution in step (3) includes any one of hydrochloric acid solution, sulfuric acid solution and nitric acid solution, with a concentration of 0.05-0.2 mol / L; the drying temperature is 50-70° C., and the drying time is 5-12 h.
9. A Fe-N5 single atom catalyst, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. Use of the Fe-N5 single atom catalyst according to claim 9 in treating organic pollutants.